Efeitos do Coaching Cognitivo-Comportamental na transição universidade-trabalho: intervenção de carreira em grupo - Gottschalk, Luciane Leila Linden (Universidade do Vale do Rio dos Sinos, 2016)
On the eve of graduation, university students live the university-work transition, with difficulties on making decisions, thus suggesting interventions that promote the career adaptability indicated at this stage. The first article verified the effects of the Cognitive-Behavioral Coaching (CBC) intervention under the dimensions of career development in a quasi-experimental study of repeated measures. A total participated 116 university students of private Higher Education Institution in Rio Grande do Sul, using the Sociodemographic Questionnaire and Career Development Scales for University Students (EDCU), Depression, Stress and Anxiety Scale (DASS-21) and Reduced Markers for Personality Assessment in the Five Large Factor Model (MR-25). After the intervention, the effects were: increased exploitation, career identity and career decision, locus of professional control and self-efficacy, with reduction of depression. The opening characteristic was presented as a differential of the participants who attended after two months of the conclusion of the intervention (follow up), and all dimensions remained without significant difference except for the self-efficacy that continued to increase in the follow up. The second article aimed to detail the protocol used in the respective program, through an intervention report. It was concluded that the effects of the CBC intervention were positive and studies that replicate the intervention are suggested.
Keywords: Transição universidade-trabalho; Coaching Cognitivo-Comportamental; Planejamento de carreira; Avaliação de programa; Relato de intervenção; University-work transition; Cognitive-Behavioural Coaching; Career planning; Program evaluation; Intervention report; ACCNPQ::Ciências Humanas::Psicologia